Xp11.2 Translocation Renal Cell Carcinoma With TFE3 Rearrangement: Distinct Morphological Features and Prognosis With Different Fusion Partners - Ge, Yan; Lin, Xingtao; Zhang, Qingling; Lin, Danyi; Luo, Luqiao; Wang, Huiling; Li, Zhi (Frontiers in Oncology, 2021)
Background: Renal cell carcinoma associated with Xp11.2 translocation/TFE3 gene fusion is a rare and new subtype of RCC and is classified by WHO in 2004. Since then, multiple 5’ fusion partners for TFE3 have been reported, however, the impact of individual fusion variant on specific clinicopathologic features of Xp11.2 RCCs has not been well defined. Methods: Four Xp11.2 translocation RCCs were identified by morphological, immunostaining and FISH assay from 200 patients who attended Guangdong General Hospital between January 2017 and January 2020. All four cases were further analyzed by RNA sequencing to explore their TFE3 gene fusion partners. The clinicopathologic features including clinical manifestations, pathological findings, treatment strategies, clinical outcomes, and follow-up information of these patients were recorded and evaluated. Results: These four cases affected one male and 3 females. The median age was 13 years at the time of diagnosis (with range from 4 to 20). All these examined tumors were unilateral and unifocal. The largest diameter of these tumors ranged from 2.0cm to 10.0cm and the average was 5.55cm. Regional lymph node or distant metastasis developed in 2 patients. Three cases demonstrated known fusions: ASPCR1-TFE3 (2 cases), PRCC-TFE3 (1 cases). However, one case showed unreported VCP-TFE3 fusion gene in Xp11.2 translocation RCCs. Immunohistochemistry results revealed tumor cells diffusely positive for TFE3 but have no consistency in other markers. Moreover, there were different clinical prognosis among different variant TFE3 rearrangements, VCP-TFE3 translocation RCC patient had worse prognosis, compared to other fusion types. Follow-up were available for all the patients and range from 3 to 36 months. Three patients were without evidence of disease progression, while VCP-TFE3 died of the disease 3 months after the diagnosis. Conclusion: In conclusion, our data expands the list of TFE3 gene fusion partners and the clinicopathologic features of Xp11.2 RCCs with specific TFE3 gene fusions. We identified a novel VCP-TFE3 fusion in Xp11.2 translocation RCCs for the first time, which has unique morphology and worse prognosis than those with other variant TFE3 rearrangement. Integration of morphological, immunohistochemical and molecular methods are often necessary for the precise diagnosis and optimal clinical management of malignant tumors.